(untitled) (BERBAKTI : Jurnal Pengabdian Kepada Masyarakat, 2023)
The activity of socializing the habit of saving from an early age is one effort to improve the awareness and financial capabilities of children. Saving is an important activity that needs to be learned from an early age in order to form good habits in financial management in the future. However, there are still shortcomings in the process of learning to save among children, especially at an early age. Therefore, the socialization activity of saving from an early age for 1st and 2nd-grade elementary school students was carried out with the aim of providing understanding and knowledge about saving to students. This activity was conducted through lectures and simulation of saving using piggy banks. Students are expected to understand the concept of saving and the benefits that can be obtained from the activity. The survey results showed that most students understand the meaning and benefits of saving and feel that the activity of socializing saving from an early age is beneficial. In addition, the teachers and school principals gave positive responses to the activity. Recommendations are given to carry out similar activities regularly every year to help improve the awareness and financial capabilities of students in the future. The activity of socializing the habit of saving from an early age for 1st and 2nd-grade elementary school students is expected to help change the mindset and behavior of students regarding financial management so that good saving habits are formed from an early age.